2021
DOI: 10.1038/s41598-021-83790-0
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid and kaolin effects on pomological, physiological, and phytochemical characters of hazelnut (Corylus avellana) at warm summer condition

Abstract: Climate change and population increase are two challenges for crop production in the world. Hazelnut (Corylus avellana L.) is considered an important nut regarding its nutritional and economic values. As a fact, the application of supporting materials as foliage sprays on plants will decrease biotic and abiotic stresses. In this study, the effects of salicylic acid (0, 1 mM and 2.5 mM) and kaolin (0, 3% and 6%) sprays were investigated on morphological, physiological, pomological, and biochemical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 85 publications
1
3
1
Order By: Relevance
“…Dinis et al [48] found that the application of kaolin spray led to an increase in photochemical reflectance and photosynthetic pigments in a grapevine plant. These results are consistent with Abdallah et al, 2019, and Khavari et al, 2021 [49,50].…”
Section: Effect Of Kaolin On the Photosynthetic Pigments Leaf Of Keit...supporting
confidence: 92%
“…Dinis et al [48] found that the application of kaolin spray led to an increase in photochemical reflectance and photosynthetic pigments in a grapevine plant. These results are consistent with Abdallah et al, 2019, and Khavari et al, 2021 [49,50].…”
Section: Effect Of Kaolin On the Photosynthetic Pigments Leaf Of Keit...supporting
confidence: 92%
“…In accordance with our results ( Table 1 ), Wang et al and Brillante et al [ 30 , 31 ] showed a positive effect of kaolin treatment on the anthocyanins content of grapes and grapewines, respectively. Contrary to our results, Khavary et al [ 32 ] showed that the kaolin treatment increased the contents of carotenoids and total chlorophyll in hazelnuts, while Brito et al [ 33 ] found no significant difference between kaolin and control treatment in carotenoids and chlorophyll contents in the leaves of olive plants. Criado et al [ 25 ] showed a concentration of total chlorophyll in a range between 3.1 mg/kg to 285 mg/kg in the Arbequina cultivar and between 1.6 mg/kg to 392 mg/kg in the Farga cultivar, depending on the ripening stage.…”
Section: Discussioncontrasting
confidence: 99%
“…SA is a phenolic compound that acts as a plant hormone and signalling molecule with beneficial effects on the resistance to many abiotic stressors, including salt (Nazar et al 2011), heat (Wang et al 2010), and drought (Iqbal et al 2022). During high-temperature stress, exogenous SA applications improve photosynthesis (Wang et al 2010), pigment concentration, and antioxidant systems by regulating enzymes, such as peroxidases, superoxide dismutase, and catalases, which lower the formation of reactive oxygen species and reduce oxidative stress (Khavari et al 2021). A foliar spray of AsA has been demonstrated to enhance plant growth and development.…”
Section: Introductionmentioning
confidence: 99%